Joint market bid of a hydroelectric system and wind parks. (March 2019) - Knežević, Goran; Topić, Danijel; Jurić, Marija; Nikolovski, Srete
Highlights: Optimization model finding market bid providing maximal profit is proposed. Two stage optimization model maximizes profit and minimizes imbalance penalties. Calculation of the expected profit considers all given operation scenarios. Abstract: This paper presents the model for finding an optimal joint bid of hydroelectric systems and wind parks on a day-ahead electricity market. The optimization problem is presented as a two-stage model where the goal of the first stage is to maximize the profit according to the main scenario and the obtained production plan is then tested in all other scenarios that can occur in the second stage where the goal is to minimize the profit reduction caused by imbalance penalties or changes in expected day-ahead prices. The optimization procedure is presented as a mixed integer linear optimization problem. The proposed model is applied in a case study in order to present the main model features. Production assembly in the case study is based on real power plants and consists of two cascade hydropower plants and two wind parks.